Subacute thyroiditis following COVID-19: A systematic review - Elahe Meftah; Rahem Rahmati; Fatemeh Zari Meidani; Sanaz Khodadadi; Kosar Chitzan-Zadeh; Fatemeh Esfahanian; Shiva Afshar (Frontiers in Endocrinology, 2023)
BackgroundSubacute thyroiditis (SAT) is a self-limiting thyroid inflammatory disease occurring specifically after upper respiratory tract infections. Since COVID-19 is a respiratory disease leading to multi-organ involvements, we aimed to systematically review the literature regarding SAT secondary to COVID-19.MethodsWe searched Scopus, PubMed/MEDLINE, Cochrane, Web of Science, ProQuest, and LitCovid databases using the terms “subacute thyroiditis” and “COVID-19” and their synonyms from inception to November 3, 2022. We included the original articles of the patients with SAT secondary to COVID-19. Studies reporting SAT secondary to COVID-19 vaccination or SAT symptoms’ manifestation before the COVID-19 infection were not included.ResultsTotally, 820 articles were retained. Having removed the duplicates, 250 articles remained, out of which 43 articles (40 case reports and three case series) with a total of 100 patients, were eventually selected. The patients aged 18–85 years (Mean: 42.70, SD: 11.85) and 68 (68%) were women. The time from the onset of COVID-19 to the onset of SAT symptoms varied from zero to 168 days (Mean: 28.31, SD: 36.92). The most common symptoms of SAT were neck pain in 69 patients (69%), fever in 54 (54%), fatigue and weakness in 34 (34%), and persistent palpitations in 31 (31%). The most common ultrasonographic findings were hypoechoic regions in 73 (79%), enlarged thyroid in 46 (50%), and changes in thyroid vascularity in 14 (15%). Thirty-one patients (31%) were hospitalized, and 68 (68%) were treated as outpatients. Corticosteroids were the preferred treatment in both the inpatient and outpatient settings (25 inpatients (81%) and 44 outpatients (65%)). Other preferred treatments were nonsteroidal anti-inflammatory drugs (nine inpatients (29%) and 17 outpatients (25%)) and beta-blockers (four inpatients (13%) and seven outpatients (10%)). After a mean duration of 61.59 days (SD: 67.07), 21 patients (23%) developed hypothyroidism and thus, levothyroxine-based treatment was used in six of these patients and the rest of these patients did not receive levothyroxine.ConclusionSAT secondary to COVID-19 seems to manifest almost similarly to the conventional SAT. However, except for the case reports and case series, lack of studies has limited the quality of the data at hand.